2005
DOI: 10.1360/04yc0011
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of arsenic and essential elements in pinna ofarsenic hyperaccumulator Pteris vittata L.

Abstract: The distributions of arsenic and 6 essential elements in the pinna of As hyperaccumulator, Pteris vittata L., were studied using synchrotron radiation X-ray fluorescence (SRXRF). Significant correlation between the distribution and mobility of the elements revealed that SRXRF study on the elemental distribution was feasible to inspect the transportations of elements in plants. The distribution of As in the pinna showed that As had great abilities to be transported in xylem vessels and from xylem to mesophyll. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…They employed synchrotron radiation Xray fluorescence spectroscopy (SRXRF) which has higher detection sensitivity than EDXA, and reported a higher As content in mesophyll as opposed to epidermal tissues, however only qualitative SRXRF images were presented. In a later study, Chen et al (2005) showed qualitative SRXRF images of intact fresh P. vittata pinna and indicated that As in the midrib efficiently translocated to surrounding mesophyll tissues, however, as in their earlier study, quantitative data were not presented. Several studies have shown that dermal localization of metals is not a universal characteristic of hyperaccumulating species and suggest that leaf tissues aside from dermal tissues, are also considered important sites for metal localization in herbaceous hyperaccumulating species.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…They employed synchrotron radiation Xray fluorescence spectroscopy (SRXRF) which has higher detection sensitivity than EDXA, and reported a higher As content in mesophyll as opposed to epidermal tissues, however only qualitative SRXRF images were presented. In a later study, Chen et al (2005) showed qualitative SRXRF images of intact fresh P. vittata pinna and indicated that As in the midrib efficiently translocated to surrounding mesophyll tissues, however, as in their earlier study, quantitative data were not presented. Several studies have shown that dermal localization of metals is not a universal characteristic of hyperaccumulating species and suggest that leaf tissues aside from dermal tissues, are also considered important sites for metal localization in herbaceous hyperaccumulating species.…”
Section: Discussionmentioning
confidence: 74%
“…However, only a few studies have addressed tolerance mechanisms, in particular localization and spatial distribution of As in storage tissues. Furthermore, these few studies have primarily focused on As localization in frond tissues and appear inconsistent as they suggest that preferential As localization may occur in epidermal (Lombi et al 2002) and mesophyll (Chen et al 2005(Chen et al , 2003 tissues. To our knowledge, there have been no studies that address As localization in stipe tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is taken up by the root, transported to the frond [68], localized to upper and lower epidermal cells and trichomes, where it is stored in the vacuoles [69]. It has been reported that hyperaccumulation of arsenic was defined as a concentration above 1000 µg.g -1 DW [70].…”
Section: As Uptakementioning
confidence: 99%
“…For instance, McNear et al (2005) found that the Ni hyperaccumulator Alyssum murale stored Ni in the base of leaf trichomes and epidermal cells, basically sequestering Ni in non-metabolically active cells to prevent toxicity. Spatially resolved metal abundance data have been used in studies of the metabolism of numerous metal hyperaccumulator plants (Sarret et al, 2002;Chen et al, 2003Chen et al, , 2005McNear et al, 2005;Onuma et al, 2005;Tongbin et al, 2005;Isaure et al, 2006;Kashiwabara et al, 2006;Scheckel et al, 2007;Tappero et al, 2007). Metal localization characteristics can reveal the plant organ in which genes are expressed, and confirm the function of transport proteins and metallochaperones responsible for moving metals across membranes and through the cell.…”
Section: Introductionmentioning
confidence: 99%